Design, modelling, and analysis of a large floating dock for spar floating wind turbine installation. (July 2020) - Jiang, Zhiyu; Yttervik, Rune; Gao, Zhen; Sandvik, Peter Christian
Abstract: Installation of floating wind turbines at the offshore site is a challenging task. A significant part of the time efficiency and costs are related to the installation methods which are sensitive to weather conditions. This study investigates a large floating dock concept, which can be used to shield a floating wind turbine during installation of tower, nacelle, and rotor onto a spar foundation. In this paper, the concept is described in detail, and a design optimisation is carried out using simple design constraints. Hydrodynamic analysis and dynamic response analysis of the coupled system of the optimum dock and spar are conducted. Two spars of different sizes are considered, and the motion responses of the spars with and without the dock in irregular waves are compared. Through analysis of the motion spectra and response statistics, dynamic characteristics of the coupled system is revealed. The present design of the dock reduces the platform-pitch responses of the spars and potentially facilitates blade mating, but may deteriorate the heave velocity of the spars in swell conditions. Finally, future design aspects of the floating dock are discussed. Highlights: A cylindrical dock concept is proposed to facilitate offshore installation of spar floating wind turbines. A design optimisation of the dock is carried out considering practical design constraints. Hydrodynamic analysis and dynamic response analysis reveal interesting characteristics of the coupled dock and spar systems. The present dock design increases the operational limits for blade mating but may face challenges under swell conditions.